2006
DOI: 10.1063/1.2335396
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of catalyst particle size during carbon single walled nanotube growth and its effect on the tube characteristics

Abstract: A series of Fe catalysts, with different mean diameters, supported on alumina with different molar ratios, was studied before and after carbon single walled nanotubes growth using magnetic measurements and Raman scattering techniques (laser excitation wavelengths from 1.17to2.54eV) to follow changes on catalyst particle size and composition, as well as the relationship between particle size and diameter of nanotubes grown. In all cases, an increase and redistribution of the particle size after the growth was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In the AFM images there are clear examples of NPs at the end of SWNTs where the particles are much larger than the SWNTs, providing direct evidence that larger NPs can catalyze the growth of smaller SWNTs. This observation is in line with previous studies that found indirect evidence that for larger catalyst particles there appeared to be no direct correlation between the catalyst size and nanotube diameter 41. It is also interesting that the SWNT network density is so insensitive to catalyst concentration.…”
Section: Resultssupporting
confidence: 92%
“…In the AFM images there are clear examples of NPs at the end of SWNTs where the particles are much larger than the SWNTs, providing direct evidence that larger NPs can catalyze the growth of smaller SWNTs. This observation is in line with previous studies that found indirect evidence that for larger catalyst particles there appeared to be no direct correlation between the catalyst size and nanotube diameter 41. It is also interesting that the SWNT network density is so insensitive to catalyst concentration.…”
Section: Resultssupporting
confidence: 92%
“…Consequently, if liquefaction was a prerequisite for catalytic activity, the small particles would begin to produce nanotubes earlier. Experimental verification of this hypothesis is challenging: very small catalyst nanoparticles (d ∼ =1 nm) have a fast rate of coalescence during the reaction and coagulate to form bigger clusters [100,101]. Following the VLS model, the growth of very small nanotubes using metallic catalyst would be possible only if the reaction temperature were above T eut (to liquefy the particle) and below the temperature at which particles begin to coalesce.…”
Section: Phase Diagram Of Free and Supported Fe-c Nanoparticlesmentioning
confidence: 99%
“…In our experiments, Fe catalysts supported on alumina powder were prepared using a the common impregnation method [14]. To find the minimum synthesis temperature, T min synth , as a function of catalyst size, different particles' dimensions were obtained by varying the Fe:Al 2 O 3 molar ratio 1:15, 1:25, 1:50 and 1:100, [24] corresponding to particles of diameters ∼ 3 ± 0.6, ∼ 2 ± 0.8, ∼ 1.4 ± 0.7, and ∼ 1.3 ± 0.7 nm, respectively. The growth of SWC-NTs was performed with CCVD at temperatures between 650-900 • C, for 90 min over the pre-reduced catalysts [25].…”
mentioning
confidence: 99%